The Influence of Market Orientation on Product Innovation in The Palm Sugar Industry in The Watchunu Sub-District and North Poleang Bombana District - Sultan, Sultan; Rianda, La; Herdhiansyah, Dhian (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
This study aims to determine the effect of market orientation on product innovation in the Palm Sugar industry in Tontonunu District and Poleang uatara Regency, Bombana Regency. The sample in this study were 38 respondents in the coconut sugar industry. This study uses multiple linear regression analysis as an analysis tool.The results of this study found that Market Orientation simultaneously had a significant effect on product innovation in the Palm Sugar industry in Tontonunu District and Poleang uatara District in Bombana Regency. Partially, market orientation and customer orientation variables have a positive and significant effect on product innovation.